2018
DOI: 10.1371/journal.pone.0197069
|View full text |Cite
|
Sign up to set email alerts
|

Allele and dosage specificity of the Peg3 imprinted domain

Abstract: The biological impetus for gene dosage and allele specificity of mammalian imprinted genes is not fully understood. To address this, we generated and analyzed four sets of mice from a single breeding scheme with varying allelic expression and gene dosage of the Peg3 domain. The mutants with abrogation of the two paternally expressed genes, Peg3 and Usp29, showed a significant decrease in growth rates for both males and females, while the mutants with biallelic expression of Peg3 and Usp29 resulted in an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…In a prior mutant model of Peg3 , reduced numbers of Oxt-expressing neurons were initially observed, which was then thought to be a main cause for the milk provision problem [ 9 ]. However, this has been later argued by two independent studies reporting that the mutations did not cause any change in the numbers of Oxt-immunoreactive neurons in the hypothalamus [ 13 , 16 , 17 ]. Nevertheless, subsequent experiments confirmed again the presence of the milk provision problem in several Peg3-KO models, and further substantiated that this defect was more pronounced through the conditional mutation of Peg3 in the mammary gland than in the hypothalamus [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a prior mutant model of Peg3 , reduced numbers of Oxt-expressing neurons were initially observed, which was then thought to be a main cause for the milk provision problem [ 9 ]. However, this has been later argued by two independent studies reporting that the mutations did not cause any change in the numbers of Oxt-immunoreactive neurons in the hypothalamus [ 13 , 16 , 17 ]. Nevertheless, subsequent experiments confirmed again the presence of the milk provision problem in several Peg3-KO models, and further substantiated that this defect was more pronounced through the conditional mutation of Peg3 in the mammary gland than in the hypothalamus [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expression levels of Zim1 were 2.0-fold up-regulated in KO2/WT relative to those from WT/WT. We have previously reported that paternal deletion of the Peg3-DMR usually causes paternal activation and subsequent bi-allelic expression of Zim1 [ 17 , 22 ]. Thus, the observed 2.0-fold up-regulation may reflect the combined contribution from both alleles with each being equally 1.0-fold [ 17 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that paternal deletion of the Peg3-DMR usually causes paternal activation and subsequent bi-allelic expression of Zim1 [ 17 , 22 ]. Thus, the observed 2.0-fold up-regulation may reflect the combined contribution from both alleles with each being equally 1.0-fold [ 17 , 22 ]. This further indicated that the expression levels of the maternal allele of Zim 1 were not affected in response to the paternal deletion of the Peg3 -DMR.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that GADD45 may play a direct role in demethylating anti-angiogenic and proautophagic gene promoters. Especially important are genes that are known to be controlled by differential methylation including paternally expressed gene 3 (Peg3) which is differentially methylated in paternal and maternal alleles (63). Notably, we have discovered that Peg3 is a master regulator of autophagy (64) and is markedly induced at both the mRNA and protein level in endothelial cells exposed to endorepellin (45).…”
Section: Endorepellin-activated Stress Axis Inhibits Angiogenesismentioning
confidence: 99%